Inflation expectations and inflation realities: a comparison of the Treasury Breakeven Inflation curve and the Consumer Price Index before, during, and after the Great Recession. - Church, Jonathan D. (Monthly Labor Review, 2019)
The article examines the extent to which market-based inflation expectations overshot or undershot actual inflation before, during, and after the Great Recession of 2007–2009. Topics discussed include information on comparison of the U.S. Treasury Breakeven Inflation (TBI) curve with the U.S. city-average, all-items Consumer Price Index for All Urban Consumers (CPI-U); market-based measure of inflation expectations; and market-based measure of inflation expectations CPI-U.